"How come I cannot fly a drone above the Prime Minister’s Office?" - criminal and civil liability of a drone operator in Poland (Ius Novum, 2018)
The developing branch of unmanned aviation is undoubtedly opening the new possibilities to aviation applications. The prospect of economic growth, technology availability, liberal regulations and decreasing costs of unmanned aerial vehicles reduce the entry threshold for more and more operators in Europe and worldwide. This trend is largely visible in Poland where the number of licensed drone operators in the third quarter of 2018 exceeded 8,500. The number of unlicensed, so-called recreational and sport users of drones, might be a few or even dozens times higher. While trained and licensed operators are most probably aware of their responsibilities and potential hazards the drone operations might create, recreational users tend to be more reluctant to fly by the book and less informed on potential liability of their actions. The new branch of long-time developed and matured aviation sector might require increased efforts of lawmakers, however, criminal and civil liability regulations concerning manned aviation can be successfully applied to unmanned aerial vehicles. The authors of this study present an overview of these regulations on the example of Polish provisions in order to confirm that the conscious use of the new technology is crucial for its further development and sustaining the liberal approach of lawmakers and other aviation users.
Keywords: aviation; aviation law; drones; drone operator